Implementation of Project-Based Learning Model to Improve Writing Skills of Descriptive Texts - Rabiatul Mukhlisin; Supardi Supardi; Usuludin Usuludin (Sumber Belajar Sejahtera, 2023)
This study aims to improve the writing skills of English descriptive texts for VII B graders at SMPN 1 Selong through the implementation of a project-based learning model. The identified problems were the low writing ability of descriptive texts among students and the lack of appropriate learning method. The research was conducted in two cycles involving 32 students of class VII B. In the first cycle, the project-based learning method was applied by providing guidance on accurate English language usage in the context of writing descriptive texts. The observation results demonstrated an increase in student activity, with the average student score improving from 57 in the pre-cycle to 68.75 in the first cycle. However, some students still did not achieve learning completeness. In the second cycle, improvement measures were taken by involving students in group discussions to improve their project ideas and content. Overall, this research highlights the effectiveness of the project-based learning method in improving students' writing ability in English descriptive texts. Student activities and learning outcomes showed significant improvements after the implementation of this learning model.